Team building Faculty of Pharmacy, group strengthening workshop / Azlinda Mohamad Nor and Assoc. Prof. Dr. Mahmathi Karuppannan - Mohamad Nor, Azlinda; Karuppannan, Mahmathi (Faculty of Pharmacy, 2023)
The group strengthening workshop/ team building comprised of various activities and strategies to improve relationships, foster trust and develop a sense of unity within the team. The program started off with ice-breaking games - these activities were designed to help team members to get to know each other, break the ice and create a comfortable atmosphere, communication and collaboration exercises, problem-solving activities, and many others. Following that, a psychology officer, Pn Nurul Izzati Shaharudin, conducted a workshop called "Positive Mindset". Pn Izzati explained how staff can develop a positive mindset and outlook on life. Positive thinking can help one stay motivated and work better with others. It reduces stress levels and boosts productivity. Pn Izzati also stressed that a growth mindset is important to develop resilience and persistence in the face of obstacles. People with a growth mindset are more likely to take risks and try new things, which can lead to greater success in life.